2019
DOI: 10.3390/catal9060520
|View full text |Cite
|
Sign up to set email alerts
|

The Catalytic Activities of Carbocyclic Fused Pyridineimine Nickel Complexes Analogues in Ethylene Polymerization by Modeling Study

Abstract: In this work, two carbocyclic fused pyridineimine nickel analogue systems (Ni1 and Ni2) with different fused member rings were investigated to reveal the relationship between catalyst structure and reaction activity. Multiple linear regression analysis was performed by means of five electronic descriptors and two steric descriptors, including the Hammett constant (F), effective net charge (Qeff), energy difference (ΔE), HOMO–LUMO energy gap (Δε1, Δε2), open cone angle (θ), and bite angle (β). Very good values … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…The descriptors are then calculated by the CODESSA software, generating around 350 descriptors for each complex. As in previous studies [39][40][41][42], there are seven selfdefined descriptors which show good correlations with catalytic activity. Therefore, these descriptors are also calculated for each complex as shown in Table S8.…”
Section: Qspr Modelingsupporting
confidence: 70%
“…The descriptors are then calculated by the CODESSA software, generating around 350 descriptors for each complex. As in previous studies [39][40][41][42], there are seven selfdefined descriptors which show good correlations with catalytic activity. Therefore, these descriptors are also calculated for each complex as shown in Table S8.…”
Section: Qspr Modelingsupporting
confidence: 70%
“…On the basis of optimized structures, the values of descriptors were calculated and are listed in Table 5 . Herein, seven descriptors are considered based on our previous studies [ 38 , 39 , 40 ], including effective net charge ( Q eff ), HOMO–LUMO energy gaps (Δ ε 1 , Δ ε 2 ), energy difference (Δ E ), Hammett constant ( F ), bite angle ( β ), and open cone angle ( θ ). The detail definition and calculation procedure of each descriptor are provided in Supplementary Materials .…”
Section: Resultsmentioning
confidence: 99%
“…Multiple regression analysis, which can provide effective information for the development of catalysts, was performed to model the performance of the catalysts [40][41][42]. Malik et al reported that the analysis results can explain the different variation trends of catalytic activities using similar catalysts [42].…”
Section: Correlation Of Observed Values To N-butene Yieldmentioning
confidence: 99%